Microwave ablation with local pleural anesthesia for subpleural pulmonary nodules: our experience - Meng, Liangliang; Wu, Bin; Zhang, Xiao; Zhang, Xiaobo; Wei, Yingtian; Xue, Xiaodong; Zhang, Zhongliang; Zhang, Xin; Li, Jing; He, Xiaofeng; Ma, Li; Xiao, Yueyong (Frontiers in Oncology, 2022)
Objectives: To explore the efficacy and safety of local pleural anesthesia (LPA) for relieving pain during microwave ablation (MWA) of pulmonary nodules in the subpleural regions. Materials and Methods: From June 2019 to December 2021, 88 patients with 97 subpleural nodules underwent percutaneous CT-guided MWA. Patients were divided into two groups according to whether LPA was applied; 53 patients with local pleural anesthesia during MWA; and 35 patients with MWA without LPA. The differences in technical success, pre-and post- and intra-operative visual analog scale (VAS) pain scores, complications of the procedure, and local progression-free survival (LPFS) between the two groups were assessed. Thus, to evaluate the efficacy and safety of MWA combined with LPA for treating subpleural nodules. Results: In this study, the procedures in all patients of both groups achieved technical success according to pre-operative planning. There was no statistically significant difference in the pre-operative VAS pain scores between the two groups. Intra-operative VAS scores were significantly higher in the non-LPA (NLPA) group than in the LPA group. They remained significantly higher in the NLPA group than in the LPA group during the short postoperative period. Analgesics were used more in the NLPA group than in the LPA group intra- and postoperatively, with a statistically significant difference, especially during the MWA procedures. The overall LPFS rates were 100%, 98.333%, 98.333%, and 98.333% at 1, 3, 6, and 12 months postoperatively in the LPA group and 100%, 97.297%, 94.595%, and 94.595% postoperatively in the NLPA group, respectively. Tumor recurrence occurred in one and two patients with lung adenocarcinoma in the LPA and NLPA groups. The incidence of pneumothorax was significantly higher in the NLPA group (25,714%, 9/35) than in the LPA group (15.094%, 8/53), and there were three cases of pleural effusion (blood collection) and one case of pulmonary hemorrhage in the NLPA group. Conclusion: Percutaneous CT-guided MWA is a safe and effective treatment for subpleural pulmonary nodules. Applying a combined LPA technique can reduce the patient's pain and complications during and after the MWA. The long-term efficacy must be verified in more patients and a longer follow-up.